Epidemiological trend of hospitalized acute and recurrent hepatitis C in Spain. (29th March 2019) - Maté-Cano, Irene; Alvaro-Meca, Alejandro; Ryan, Pablo; Diaz, Asuncion; Martínez-Román, Paula; Sánchez-Carrillo, Marta; Resino, Salvador; Briz, Verónica
Abstract : Introduction: Acute hepatitis C virus (HCV) infection (AHC) is often difficult to identify due to the lack of symptoms (around 85% of cases) [1, 2 ]. Despite the decline of HCV transmission via blood-to-blood due to donor screening programs and a decline in intravenous drug use (IDUs) [3 ], the incidence of sexual transmission has now increased, particularly in human immunodeficiency virus (HIV)-infected men who have sex with men (MSM), arousing great interest in this new public health problem [4, 5 ]. This is the first study to evaluate the incidence of hospital admissions and mortality related to admitted AHC and AHC recurrences, with particular attention to HIV-infected patients, as well as to analyze its trend through the combination antiretroviral therapy (cART) era (1997–2012) in Spain. Materials and methods: We performed a retrospective study on patients with an AHC diagnosis in the Spanish Minimum Basic Data Set (MBDS). Patients were classified as HCV-monoinfected patients and HIV/HCV-coinfected patients. The outcome variables were: i) AHC-related hospital admission; ii) AHC-related mortality (intra-hospital mortality); iii) hospital admissions related to AHC recurrences. The data were treated with full confidentiality, according to Spanish legislation. MBDS is regulated by an organic law that sets out how institutions must proceed with health-related personal data. Informed consent is not required because personal data are collected for the exercise of the functions proper to public administrative bodies. The Spanish Ministry of Health confirmed that our study fulfilled all the appropriate ethical considerations, according to Spanish legislation. Results: Overall, 5792 patients were diagnosed with AHC during the study period, 4831 subjects were HCV-monoinfected, 961 individuals were HIV/HCV-coinfected and there were 115 (1.99%) recurrences, of them, 97 (2.00%) were HVC monoinfected and 18 (1, 88%) HIV/HCV coinfected, showing similar incidence in both groups. The incidence of AHC-related hospital admission in HIV/HCV-coinfected patients was 0.81 per 10, 000 person-years (p-y) while in HCV-monoinfected, it was 1.2 per 100, 000 p-y (p < 0.001). Both groups showed a dramatic decrease in hospital admissions during the study period (p < 0.001). The mortality over the whole follow-up in the HIV/HCV-coinfected group was 2.2 per 10, 000 p-y, while in the HCV-monoinfected group it was 2.0 per 100, 000 p-y (p < 0.001). AHC-related mortality diminished significantly in both groups (approximately 2–3 times) during the study period (p < 0.001). The adjusted likelihood of death for AHC was 1.90 (95%CI =2.07–3.02) times higher in HIV/HCV-coinfected patients than in HCV-monoinfected. The adjusted likelihood of AHC recurrence during the follow-up was 1.31 times higher in HIV/HCV-coinfected patients than in HCV-monoinfected patients [adjusted hazard ratio (aHR) = 1.31 (95%CI = 1.05–1.63); p = 0.013]. Discussion and conclusions: HIV/HCV-coinfected individuals were at higher risk of hospital admissions and deaths related to AHC during the cART era, with higher incidence and mortality than HCV-monoinfected subjects. Recurrence of AHC-related to hospital admissions was observed.